-4(6x-2)=x-2

Simple and best practice solution for -4(6x-2)=x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(6x-2)=x-2 equation:



-4(6x-2)=x-2
We move all terms to the left:
-4(6x-2)-(x-2)=0
We multiply parentheses
-24x-(x-2)+8=0
We get rid of parentheses
-24x-x+2+8=0
We add all the numbers together, and all the variables
-25x+10=0
We move all terms containing x to the left, all other terms to the right
-25x=-10
x=-10/-25
x=2/5

See similar equations:

| 0.02+–3m=16.82 | | V=1/33.14r^2 | | -20-15f=-13f+19+f | | 4=-3x-10 | | 3.06(x+1)=9.18 | | 7v-7v=-6(v-6)+3(v-8) | | 6x+2)+40=90 | | -10=1x/5 | | 32x+108=8x–4 | | x+3+2x+7=-2 | | e=36-8.4(2800) | | f(10)=40-7 | | -3x+1=12-5x | | 32x+108+8x-4=21x+118 | | 3x-9=-12-3x | | 7-x=15-2x | | -5-2x-7=3x-3+4x | | 4c-2=3c+1 | | x*2-1=8 | | -30x+4=20 | | 8+2x=-7x+8x | | 0.0168=c^2 | | r÷2=9 | | -20-2x=10 | | 3x(2x+5)=6x-13 | | a+8+a-4=-4(a-3)+5(a-1) | | 9x-7+65=180 | | w/2+3=w/4-5 | | 3(6x+2)-10=2+12x | | 3k-5=-2 | | 22=-(-5x-2) | | 13(x-4)=65 |

Equations solver categories